ОРГАНІЗАЦІЯ ТА ФУНКЦІЇ ПРАВООХОРОННИХ ОРГАНІВ У СФЕРІ ПРОТИДІЇ ЕКСТРЕМІЗМУ - Гожій, Вікторія Дмитрівна (SUPREMANCE OF LAW, 2018)
The article analyzes the organization and functions of law enforcement agencies in the field of counteraction to extremism. It is proved that the leading role in counteracting extremist activity belongs, first of all, to the Security Service of Ukraine and the National Police. The above conclusion is confirmed by the organizational and legal status of the indicated law enforcement bodies among the subjects of counteraction to extremist activity and law enforcement functions in relation to the implementation of such counteraction. The Strategy of National Security of Ukraine, which defines the main directions of the state policy of national security of Ukraine, is described. The tasks addressed to the Security Service of Ukraine are solved, one of which is the need to neutralize separatist and extremist movements and organizations. The competence of the National Police of Ukraine, which takes measures aimed at the improvement of the criminal situation, is analyzed. The key role of the Offi ce of Public Prosecutor in the fi eld of counteraction to extremism was established, which is to increase the effectiveness of procedural guidance for pre-trial investigation and coordination of law enforcement agencies in the fi eld of counteraction to extremist offenses.
Keywords: law enforcement agencies; counteraction to extremism; Security Service of Ukraine; National Police; subjects of counteraction to extremist activity; pre-trial investigation; competence; prosecutor’s office; National Security Strategy of Ukraine